Towards Oligonucleotide Pro-Drugs: 2,2-Bis(ethoxycarbonyl) and 2- (Alkylaminocarbonyl)-2-cyano Substituted 3-(Pivaloyloxy)Propyl Groups as Biodegradable Protecting Groups for Internucleosidic Phosphoromonothioate Linkages - Poijarvi, P.; Oivanen, M.; Lonnberg, H. (Letters in Organic Chemistry, 2004)
The applicability of 2,2-bis(ethoxycarbonyl)-3-(pivaloyloxy)propyl and 2- cyano-2-(2-phenylethylaminocarbonyl)-3-(pivaloyloxy)propyl groups as biodegradable protecting agents for the internucleosidic linkages of phosphorothioate antisense oligonucleotides has been studied. For this purpose, protected phosphoromonothioates of thymidylyl-(3'→5')-thymidine [Tp(s)T] containing either a bridged or non-bridged sulfur atom have been prepared, and their chemical stability and enzymatic deprotection have been studied.
Keywords: hydrolysis